Antimicrobial Resistance of Salmonella enterica Serovars Typhi and Paratyphi Isolates from a General Hospital in Karawaci, Tangerang, Indonesia: A Five-Year Review - Nata Pratama Hardjo Lugito; Cucunawangsih (International Journal of Microbiology)
Typhoid and paratyphoid fever known as enteric fever pose important global public health problem, with 21.6 million cases and approximately 250,000 deaths annually. It is a prevalent disease in Indonesia, but data on the antimicrobial resistance pattern is limited. This study aim was to provide data on the antimicrobial resistance pattern of S. Typhi and S. Paratyphi bloodstream isolates in a general hospital in Karawaci, Tangerang, Banten, Indonesia, during the period of January 2011 to December 2015. Susceptibility against antimicrobials was detected according to the guidelines of the Clinical and Laboratory Standards Institute (CLSI). Out of a total of 168 isolates 55.4% were S. Typhi and 44.6% S. Paratyphi A. Most of the isolates, 92.9%, were from children aged 6–18 years and adult population. There was low resistance of S. Typhi against ampicillin, trimethoprim-sulfamethoxazole, ceftriaxone, ciprofloxacin, and levofloxacin, similar to previous studies in Indonesia. In the 2011–2015 period, resistance rates against most antimicrobials and MDR rate of S. Typhi and S. Paratyphi were low, emphasizing that there is a distinct epidemiological dynamic of the enteric fever in Indonesia.